ANALISIS KEBERHASILAN PRODUKTIVITAS JIG TERTIER PADA PROSES KONSENTRASI BIJIH TIMAH DI KAPAL KERUK BEMBAN PT. KOBA TIN, KOBA, BANGKA TENGAH - Sukamto, Untung; Rosita, Alfitri (PROMINE, 2014)
Criteria of Jig Tertierâs productivity success, namely grade, recovery, and ratio of concentration in order to qualify the target of the company, whichÂ  is having 30-40% Sn grade and recovery â¥ 97%.Regarding the initial condition of jig tertier in the concentrating process on the dredge, there is often a deadlock in the screening due to the clogging of gravels. There is also a lot of ragging whose shape and relative density do not match. The length and the frequency of the stroke is also too fast, leaving the soft tin minerals with no chance to precipitate, thus it is carried away into tailing. This problem Â leads Â the Â researcher Â to Â make Â a Â studyÂ  that Â aims Â to Â enhance Â the performance of jig, so that the company can accomplish its target, by doing an experiment of change in variables of jig tertier, which are length and frequency of the Â strokeÂ  as Â well Â as Â theÂ  maintenanceÂ  ofÂ  the Â ragging Â and Â the Â screen. Â Other variables are assumed constant.Initially, the length of the stroke in jig tertier port is 4-5 mm, and in jig tertier starboard 5-5 mm. The frequency of jig tertier port and jig tertier starboard is around180-190 spm. The grade and recovery in jig tertier port are not meeting the desired target which is 24,25% grade with 76,6% recovery. The grade in Jig Tertier Starboard is 39,13% with 46,0% recovery.An experiment is done by altering the stroke length variable into 7-8 mm in jig tertier port, and 7-7 mm in starboard, with portâs or starboardâs frequency of 160-180 spm. The maintenance in ragging is done by selecting the size and weight of the hematite stones ragging from 4,2-4,5. The experiment resulted in an improvement in jig tertier portâs grade, which increased to 42.18% Sn with 98.2% recovery. The grade in jig tertier starboard turned into 45,49% Sn with 98.1% recovery, thus the company has achieved the desired target.Â Key Word : Concentration, Jig, Grade, Ratio of Concentration and Recovery